EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN MODEL EXPERIENTIAL LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SMP NEGERI 38 PALEMBANG - Sekar Ardhanun; Karoma; Ervin Efriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Student learning motivation is strongly influenced by the teaching methods applied in the classroom. The use of conventional approaches dominated by lecture-based instruction often fails to attract students’ attention, especially in Islamic Religious Education (PAI) learning. This condition leads to low motivation and limited student participation during the learning process. To address this issue, the Experiential Learning model is introduced as an interactive, experience-based learning approach. This model emphasizes active student engagement through various activities such as simulations, role-playing, group discussions, and reflective learning. Through these activities, students are expected not only to become more motivated but also to develop a deeper and more meaningful understanding of PAI material. This study employed an experimental method with a Nonequivalent Control Group design and a quantitative approach. The research population consisted of 68 eighth-grade students at SMP Negeri 38 Palembang in the 2024/2025 academic year. The sample included class VIII.A as the experimental group and class VIII.B as the control group, selected through cluster sampling techniques. Data were collected using a motivation questionnaire containing 25 items administered before and after the learning intervention. The research findings indicate that the N-Gain score of the experimental class was 2.4532, which falls into the high category, demonstrating a significant increase in student learning motivation. The paired sample t-test also revealed a sig. (2-tailed) value of 0.024 < 0.05, leading to the rejection of H0 and acceptance of Ha. Therefore, it can be concluded that the Experiential Learning model is effective in enhancing students’ learning motivation in PAI subjects.